src/HOL/ex/Cubic_Quartic.thy
author wenzelm
Tue, 12 Apr 2016 14:38:57 +0200
changeset 62958 b41c1cb5e251
parent 62390 842917225d56
child 63054 1b237d147cc4
permissions -rw-r--r--
Type_Infer.object_logic controls improvement of type inference result;

(*  Title:      HOL/ex/Cubic_Quartic.thy
    Author:     Amine Chaieb
*)

section "The Cubic and Quartic Root Formulas"

theory Cubic_Quartic
imports Complex_Main
begin

section "The Cubic Formula"

definition "ccbrt z = (SOME (w::complex). w^3 = z)"

lemma ccbrt: "(ccbrt z) ^ 3 = z"
proof-
  from rcis_Ex obtain r a where ra: "z = rcis r a" by blast
  let ?r' = "if r < 0 then - root 3 (-r) else root 3 r"
  let ?a' = "a/3"
  have "rcis ?r' ?a' ^ 3 = rcis r a" by (cases "r<0", simp_all add: DeMoivre2)
  hence th: "\<exists>w. w^3 = z" unfolding ra by blast
  from someI_ex[OF th] show ?thesis unfolding ccbrt_def by blast
qed

text "The reduction to a simpler form:"

lemma cubic_reduction:
  fixes a :: complex
  assumes H: "a \<noteq> 0 \<and> x = y - b / (3 * a) \<and>  p = (3* a * c - b^2) / (9 * a^2) \<and>  
              q = (9 * a * b * c - 2 * b^3 - 27 * a^2 * d) / (54 * a^3)"
  shows "a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow> y^3 + 3 * p * y - 2 * q = 0"
proof-
  from H have "3*a \<noteq> 0" "9*a^2 \<noteq> 0" "54*a^3 \<noteq> 0" by auto
  hence th: "x = y - b / (3 * a) \<longleftrightarrow> (3*a) * x = (3*a) * y - b" 
            "p = (3* a * c - b^2) / (9 * a^2) \<longleftrightarrow> (9 * a^2) * p = (3* a * c - b^2)"
            "q = (9 * a * b * c - 2 * b^3 - 27 * a^2 * d) / (54 * a^3) \<longleftrightarrow> 
             (54 * a^3) * q = (9 * a * b * c - 2 * b^3 - 27 * a^2 * d)"
    by (simp_all add: field_simps)
  from H[unfolded th] show ?thesis by algebra
qed

text "The solutions of the special form:"

lemma cubic_basic: 
  fixes s :: complex
  assumes H: "s^2 = q^2 + p^3 \<and>
              s1^3 = (if p = 0 then 2 * q else q + s) \<and>
              s2 = -s1 * (1 + i * t) / 2 \<and>
              s3 = -s1 * (1 - i * t) / 2 \<and>
              i^2 + 1 = 0 \<and>
              t^2 = 3"
  shows 
    "if p = 0
     then y^3 + 3 * p * y - 2 * q = 0 \<longleftrightarrow> y = s1 \<or> y = s2 \<or> y = s3
     else s1 \<noteq> 0 \<and>
          (y^3 + 3 * p * y - 2 * q = 0 \<longleftrightarrow> (y = s1 - p / s1 \<or> y = s2 - p / s2 \<or> y = s3 - p / s3))"
proof-
 { assume p0: "p = 0"
   with H have ?thesis by (simp add: field_simps) algebra
 }
 moreover
 { assume p0: "p \<noteq> 0"
   with H have th1: "s1 \<noteq> 0" by (simp add: field_simps) algebra
   from p0 H th1 have th0: "s2 \<noteq> 0" "s3 \<noteq>0"
     by (simp_all add: field_simps) algebra+
   from th1 th0 
   have th: "y = s1 - p / s1 \<longleftrightarrow> s1*y = s1^2 - p"
            "y = s2 - p / s2 \<longleftrightarrow> s2*y = s2^2 - p"
            "y = s3 - p / s3 \<longleftrightarrow> s3*y = s3^2 - p"
     by (simp_all add: field_simps power2_eq_square) 
   from p0 H have ?thesis unfolding th by (simp add: field_simps) algebra
 }
 ultimately show ?thesis by blast
qed

text "Explicit formula for the roots:"

lemma cubic:
  assumes a0: "a \<noteq> 0"
  shows "
  let p = (3 * a * c - b^2) / (9 * a^2) ;
      q = (9 * a * b * c - 2 * b^3 - 27 * a^2 * d) / (54 * a^3);
      s = csqrt(q^2 + p^3);
      s1 = (if p = 0 then ccbrt(2 * q) else ccbrt(q + s));
      s2 = -s1 * (1 + ii * csqrt 3) / 2;
      s3 = -s1 * (1 - ii * csqrt 3) / 2
  in if p = 0 then 
       a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow>
           x = s1 - b / (3 * a) \<or>
           x = s2 - b / (3 * a) \<or>
           x = s3 - b / (3 * a)
      else
        s1 \<noteq> 0 \<and>
        (a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow>
            x = s1 - p / s1 - b / (3 * a) \<or>
            x = s2 - p / s2 - b / (3 * a) \<or>
            x = s3 - p / s3 - b / (3 * a))"
proof-
  let ?p = "(3 * a * c - b^2) / (9 * a^2)"
  let ?q = "(9 * a * b * c - 2 * b^3 - 27 * a^2 * d) / (54 * a^3)"
  let ?s = "csqrt(?q^2 + ?p^3)"
  let ?s1 = "if ?p = 0 then ccbrt(2 * ?q) else ccbrt(?q + ?s)"
  let ?s2 = "- ?s1 * (1 + ii * csqrt 3) / 2"
  let ?s3 = "- ?s1 * (1 - ii * csqrt 3) / 2"
  let ?y = "x + b / (3 * a)"
  from a0 have zero: "9 * a^2 \<noteq> 0" "a^3 * 54 \<noteq> 0" "(a*3)\<noteq> 0" by auto
  have eq:"a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow> ?y^3 + 3 * ?p * ?y - 2 * ?q = 0"
    by (rule cubic_reduction) (auto simp add: field_simps zero a0)
  have "csqrt 3^2 = 3" by (rule power2_csqrt)
  hence th0: "?s^2 = ?q^2 + ?p ^ 3 \<and> ?s1^ 3 = (if ?p = 0 then 2 * ?q else ?q + ?s) \<and>
              ?s2 = - ?s1 * (1 + ii * csqrt 3) / 2 \<and> 
              ?s3 = - ?s1 * (1 - ii * csqrt 3) / 2 \<and> 
              ii^2 + 1 = 0 \<and> csqrt 3^2 = 3"
    using zero by (simp add: field_simps ccbrt)
  from cubic_basic[OF th0, of ?y]
  show ?thesis 
    apply (simp only: Let_def eq)
    using zero apply (simp add: field_simps ccbrt)
    using zero
    apply (cases "a * (c * 3) = b^2", simp_all add: field_simps)
    done
qed


section "The Quartic Formula"

lemma quartic:
 "(y::real)^3 - b * y^2 + (a * c - 4 * d) * y - a^2 * d + 4 * b * d - c^2 = 0 \<and>
  R^2 = a^2 / 4 - b + y \<and>
  s^2 = y^2 - 4 * d \<and>
  (D^2 = (if R = 0 then 3 * a^2 / 4 - 2 * b + 2 * s
                   else 3 * a^2 / 4 - R^2 - 2 * b + (4 * a * b - 8 * c - a^3) / (4 * R))) \<and>
  (E^2 = (if R = 0 then 3 * a^2 / 4 - 2 * b - 2 * s
                   else 3 * a^2 / 4 - R^2 - 2 * b - (4 * a * b - 8 * c - a^3) / (4 * R)))
  \<Longrightarrow> x^4 + a * x^3 + b * x^2 + c * x + d = 0 \<longleftrightarrow>
      x = -a / 4 + R / 2 + D / 2 \<or>
      x = -a / 4 + R / 2 - D / 2 \<or>
      x = -a / 4 - R / 2 + E / 2 \<or>
      x = -a / 4 - R / 2 - E / 2"
apply (cases "R=0", simp_all add: field_simps divide_minus_left[symmetric] del: divide_minus_left)
 apply algebra
apply algebra
done

end